Experimental study on the axial compressive strength of vertical inner plate reinforced square hollow section T-joints. (1st October 2018) - Chang, Hongfei; Xia, Junwu; Guo, Zhen; Hou, Chao; Din, Wei; Qin, Fuyang
Highlights: The compressive behavior of vertical inner plate reinforced SHS T-joints is studied experimentally. The finite element model of VIPR SHS T-joint is built and verified. The mechanism of the vertical inner plate reinforcement is discussed. Equations to estimate the compressive strength of VIPR SHS T-joint are proposed. Abstract: To evaluate the influence of vertical inner plate reinforcement on the compression behavior of square hollow section joints, four T-joints with and without such reinforcement were tested experimentally and simulated numerically. The experimental set-up and failure sequences are described while the strain distribution, load-displacement curves, compressive strength as well as the failure modes of the joints are analyzed. The test results demonstrate that the vertical inner plate is effective to enhance the compressive strength of the SHS T-joints, yet the efficiency of the reinforcement decreases with the increase of the width ratio between the brace and the chord. Meanwhile, the presence of the vertical inner plate has little influence on the strain distribution and failure mode of the joint. The failure of the vertical inner plate reinforced T-joints is dominated by two modes, namely flange yielding and web buckling. The yielding of the chord flange will dominate for joints with small brace-chord width ratio, and the combination of flange yielding and web buckling will dominate for joints with large brace-chord width ratio. The numerical models of the specimens are developed and used to reveal the mechanism of the vertical inner plate to increase the compressive strength of the joint. The function of the vertical inner plate can be divided into two aspects, one is to enlarge the yielding scope at the top flange of the chord, and the other is to drive the yielding at the bottom flange of the chord. The proposed equation achieves a good estimation for the compressive strength of the vertical inner plate reinforced joint.